2011
DOI: 10.1186/1471-2458-11-396
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of breastfeeding and complementary feeding practices in urban informal settlements, Nairobi Kenya

Abstract: BackgroundThe World Health Organisation (WHO) recommends exclusive breastfeeding during the first six months of life for optimal growth, development and health. Breastfeeding should continue up to two years or more and nutritionally adequate, safe, and appropriately-fed complementary foods should be introduced at the age of six months to meet the evolving needs of the growing infant. Little evidence exists on breastfeeding and infant feeding practices in urban slums in sub-Saharan Africa. Our aim was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
205
12
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(262 citation statements)
references
References 41 publications
37
205
12
8
Order By: Relevance
“…Maternal level of education has also been reported to influence exclusive breastfeeding by some studies. 18,22 However, other studies did not find a significant association.…”
Section: Socioeconomic Factorsmentioning
confidence: 61%
See 1 more Smart Citation
“…Maternal level of education has also been reported to influence exclusive breastfeeding by some studies. 18,22 However, other studies did not find a significant association.…”
Section: Socioeconomic Factorsmentioning
confidence: 61%
“…24 In another study in Nairobi informal settlements, child's sex was among the predictors of early introduction of complementary foods. 22 The age of the infant has also been significantly associated with exclusive breastfeeding. In a study carried out in Nyando, the rate of exclusive breastfeeding decreased with an increase in infant age.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The first section of the interview schedule consisted the questions on the socio-demographic profile, educational status of the respondents which included question about the age of the respondent, religion, caste, migration status of the respondent, Ownership of household, Type of family, Years of education of the respondent, Years of education of the respondent's husband, etc. were asked [31][32][33][34][35].…”
Section: Methodsologymentioning
confidence: 99%
“…44 On the contrary, factors associated with sub-optimal infant feeding practices in urban informal settlements in Nairobi, Kenya, included the child's gender, perceived size at birth, mother's marital status, ethnicity, education level, family planning (pregnancy desirability), health seeking behaviour (place of delivery) and neighbourhood (slum of residence). 45 Infant feeding practices in the context of HIV differ from that within the general population. A study comparing data from two cross-sectional surveys conducted in Eastern Uganda has demonstrated that EBF of infants under the age of 6 months was more common in the general population (54%) than among the HIV-positive mothers (24%).…”
Section: Child Healthmentioning
confidence: 99%